2022
DOI: 10.4014/jmb.2206.06012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic Fermented Fruit Juice-Based Biotransformation by Lactic Acid Bacteria and Saccharomyces boulardii CNCM I-745 on Anti-Salmonella and Antioxidative Properties

Abstract: Recently, consumer awareness of healthy foods and eating habits has generated a massive market demand for functional foods with health benefits. Fermented foods, particularly non-dairy beverages, are gaining popularity and acceptance due to their functional benefits [1].Biotransformation based on fermentation is controlled by two main factors, microorganisms and substrates [2]. Lactic acid bacteria (LAB) and yeast are the most used probiotics in fermented foods. Some species of yeast, including Saccharomyces c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…They can exhibit various properties such as antimicrobial, antifungal, antiparasitic, antiviral, antiallergenic, anti-inflammatory and chemotherapeutic and are also used as flavoring and aromatic substances in the food and cosmetic industries [ 96 ]. Since the ability of LAB to synthesize terpenes is not described thoroughly [ 97 , 98 ], the presence of genes involved in terpenes’ synthesis found in all analyzed metagenomes was intriguing. β-lactones, cyclic carboxylic esters with four-membered rings, have a unique feature in the form of highly reactive electrophilic scaffolds and serve as versatile synthetic intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…They can exhibit various properties such as antimicrobial, antifungal, antiparasitic, antiviral, antiallergenic, anti-inflammatory and chemotherapeutic and are also used as flavoring and aromatic substances in the food and cosmetic industries [ 96 ]. Since the ability of LAB to synthesize terpenes is not described thoroughly [ 97 , 98 ], the presence of genes involved in terpenes’ synthesis found in all analyzed metagenomes was intriguing. β-lactones, cyclic carboxylic esters with four-membered rings, have a unique feature in the form of highly reactive electrophilic scaffolds and serve as versatile synthetic intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic acid inhibits the growth of LABs mainly by disrupting their cell wall and membrane structure, further reducing microbial acid production and carbohydrate utilisation [33]. Whereas, Laosee et al recently revealed that the growth of LABs can be promoted by polyphenolic-rich fruit juices [34]. Therefore, it is important to choose a suitable procyanidin concentration to observe the biotransformation model of LABs.…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant decrease in the pH value during storage was observed in the control sample. After 72 h, the value of this parameter decreased by 0.4, which could be related to the growth and acidifying effect of the juice microflora (Table 3) [52]. The results are expressed as the mean ± standard deviation; different letters mean statistically significant differences (p ≤ 0.05); A,B,C -effect of storage time, a,b,c,d,e -effect of treatment.…”
Section: The Acidity (Ph) and Total Soluble Solids Values ( • Brix)mentioning
confidence: 93%